2019
DOI: 10.1016/j.aca.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and robust MALDI-TOF-MS glycomics analysis enabled by Girard's reagent T on-target derivatization (GTOD) of reducing glycans

Abstract: Sensitive glycomics analysis by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) is of great importance but significantly hampered by their low ionization efficiency and labile sialic acid moieties. Chemical derivatization offers a viable way to improve both the ionization efficiency and analytical sensitivity of the glycans in MS analysis by altering their hydrophobicity or charge property. Here we employed Girard's reagent T (GT) for on-target derivatization (GTOD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…The presence of trimethylamine in the GT compound can increase the positive charge on the cryptobrachytone bonds with the GT, increasing the sensitivity to detection by MS. So, cryptobrachytone C would ionize to the maximum (Zhang et al 2019). Derivatization and MS/MS technique showed that cryptobrachytone C could be extracted by α-CHCA optimally in m/z 343.17.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of trimethylamine in the GT compound can increase the positive charge on the cryptobrachytone bonds with the GT, increasing the sensitivity to detection by MS. So, cryptobrachytone C would ionize to the maximum (Zhang et al 2019). Derivatization and MS/MS technique showed that cryptobrachytone C could be extracted by α-CHCA optimally in m/z 343.17.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, typically neutral HMOs and N-/O-glycans can be quantified using MALDI-MS because of unstable sialic acid residues found in HMOs and glycoconjugates. However, sialic acids can be derivatized by certain methods to make them more stable during the MALDI-MS analysis (134).…”
Section: Challenges In the Study And Characterization Of N-glycansmentioning
confidence: 99%
“…As a result, increased levels of tri‐antennary, tetra‐antennary, and galactosylated glycan structures were observed. Compared with the in‐tube derivatization approach where sample loss easily occurs because of the labor‐intensive sample preparation and incomplete derivatization, the on‐target derivatization approach effectively overcame these aspects using specific matrix 3‐aminoquinoline or Girard's reagent T …”
Section: Ms Analysis Of Clinical Biomoleculesmentioning
confidence: 99%